On belonging and becoming in the settler-colonial city: Co-produced futurities, placemaking, and urban planning in the United States. (2nd July 2020) - Barry, Janice; Agyeman, Julian
ABSTRACT: With a few notable exceptions, settler-colonial theory has not been applied to the study of U.S. cities and urban planning. Settler-colonial theory is a relatively new field of scholarship that interrogates the destruction of Indigenous laws, ways of knowing, and connections to place to make way for a new settler futurity. This futurity is particularly pronounced in cities, where Indigenous peoples have been rendered almost completely invisible and where their opportunities to shape urban development are highly circumscribed. We use settler-colonial theory, as well as Indigenous scholars' responses to it, to extend ideas of belonging and becoming in urban planning and placemaking. We turn to the theory and practice of co-production as one possible intervention into how the relationships between Indigenous and non-Indigenous placemakers could be conceived and enacted in the urban environment.